ENGLISH LANGUAGE TEACHING AND TEACHER TRAINING AT THE UNIVERSITY OF PORTO AND PAVLO TYCHYNA UMAN STATE PEDAGOGICAL UNIVERSITY: COMPARATIVE ANALYSIS - Komar, Oleh (Studies in Comparative Education, 2022)
The article presents the comparative analysis of the English language teaching and teacher training at the University of Porto and Pavlo Tychyna Uman State Pedagogical University. Special attention and requirements to the English language teaching and training of English language teachers in the modern society are outlined. Special features of the work of the language departments of the respective universities are distinguished; their curricula, language and training programs, content of language teaching, and teacher training courses are analyzed and compared. Principles of organizing groups, number of students in the class, duration of the class, types of classes, principles of teaching practice organization, and peculiarities of student-teacher-supervisor co-operation are introduced in the article. Suggestions for implementation of the positive experience in the Ukrainian educational system are given.